2007
DOI: 10.1590/s0102-86502007000500010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased intra-abdominal pressure on the healing process after surgical stapling of the stomach of dogs

Abstract: PURPOSE: To assess the initial healing after surgical stapling of the stomach using a linear cutting stapler and creating pneumoperitoneum (12-14 mmHg) for 60 minutes or 120 minutes, and compare it with the healing of a staple line not submitted to increased pressure. METHODS: A total of 30 dogs were divided into three groups of 10 animals each: Group I (control group - surgical stapling), Group II (surgical stapling and increased intra-abdominal pressure for 60 minutes) and Group III (surgical stapling and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The para‐anastomotic adhesion formation was recorded by naked eyes according to the following standard: 14 Level 0, no adhesion; Level 1, the adhesion was thin and could be easily separated with gentle traction; Level 2, the adhesion was limited at the site of anastomosis, and was thick and could not be separated easily by bluntness; Level 3, there was extensive adhesion beyond the para‐anastomotic site, and involved in neighboring tissues, requiring significant traction or sharp dissection to separate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The para‐anastomotic adhesion formation was recorded by naked eyes according to the following standard: 14 Level 0, no adhesion; Level 1, the adhesion was thin and could be easily separated with gentle traction; Level 2, the adhesion was limited at the site of anastomosis, and was thick and could not be separated easily by bluntness; Level 3, there was extensive adhesion beyond the para‐anastomotic site, and involved in neighboring tissues, requiring significant traction or sharp dissection to separate.…”
Section: Methodsmentioning
confidence: 99%
“…It can cement tissue wounds closely, and minimize tissue damage, foreign‐body reaction and surgical‐wound infection caused by traditional suture materials. Recent reports have demonstrated that OCA can be used in colon anastomosis and femoral artery in rats, with a significantly higher bursting pressure than the traditional suture group, and now it has been widely used in clinical practice 9,10,13 –17 . However, little has been reported regarding a non‐suture technique for rabbit oviduct anastomosis using OCA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation